2006
DOI: 10.1007/s11120-006-9042-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the three isoforms of the light-harvesting complex II using transient absorption and time-resolved fluorescence measurements

Abstract: In this article we report the characterization of the energy transfer process in the reconstituted isoforms of the plant light-harvesting complex II. Homotrimers of recombinant Lhcb1 and Lhcb2 and monomers of Lhcb3 were compared to native trimeric complexes. We used low-intensity femtosecond transient absorption (TA) and time-resolved fluorescence measurements at 77 K and at room temperature, respectively, to excite the complexes selectively in the chlorophyll b absorption band at 650 nm with 80 fs pulses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
42
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 54 publications
14
42
1
Order By: Relevance
“…In another recent study by Schlau-Cohen et al [115] a sub-110 fs relaxation process through spatially overlapping states was detected that had not been observed before but all the slower processes that were observed were in excellent agreement with previous results. It should be noticed that although all theoretical models are based on the structural model of Lhcb1, the (sub)ps transient absorption kinetics of three gene products forming LHCII, Lhcb1, Lhcb2 and Lhcb3, are identical [116].…”
Section: Energy Transfer In the Antenna Complexes Of Photosystem IImentioning
confidence: 99%
“…In another recent study by Schlau-Cohen et al [115] a sub-110 fs relaxation process through spatially overlapping states was detected that had not been observed before but all the slower processes that were observed were in excellent agreement with previous results. It should be noticed that although all theoretical models are based on the structural model of Lhcb1, the (sub)ps transient absorption kinetics of three gene products forming LHCII, Lhcb1, Lhcb2 and Lhcb3, are identical [116].…”
Section: Energy Transfer In the Antenna Complexes Of Photosystem IImentioning
confidence: 99%
“…The time constant of the major component of energy transfer from chlorophyll b to chlorophyll a was reported in the literature to be about 600 fs. 3,[45][46][47][48] Time constants obtained for 542 nm are 4.76 ± 1 ps and 43 ± 6 ps, again the latter value is less accurate due to the limited range of the experimental measurement. This broadband feature, from 500 nm to 600 nm (with peak at 542 nm), is related to the relaxation of the vibrational energy of the excited state of the chlorophyll molecules.…”
Section: Research Articlesmentioning
confidence: 91%
“…Several studies on the energy transfer between the chlorophylls have shown that the transfer usually takes place from chlorophyll b to chlorophyll a. 3,45 In addition to the transfer from chlorophyll b to chlorophyll a, there is also energy equilibration that takes place from chlorophyll a to chlorophyll a and from chlorophyll b to chlorophyll b. The LHC II monomer is composed of 7-8 chlorophyll a molecules, 4-5 chlorophyll b molecules and 3 carotenoids, at a chlorophyll a:b ratio of 1.6:2.…”
Section: Light-harvesting Complex IImentioning
confidence: 99%
See 2 more Smart Citations